Regional airborne gravity surveys in Western Australia: Considerations for the end user. Issue 1 (1st December 2019) - Bates, Martin; Elieff, Stefan; Kaski, Krista; Howard, David; Brett, John; Lane, Richard
Summary: Regional airborne gravity surveys are being acquired over much of the State of Western Australia by the Geological Survey of Western Australia (GSWA) and Geoscience Australia (GA) to provide coverage where existing ground gravity coverage is sparse. The acquisition and processing of these surveys poses several challenges. The data acquired by Sander Geophysics (SGL) using the AIRGrav system in Western Australia during 2018 was done so without control lines for reasons of cost efficiency, relying on the ground gravity to provide the necessary levelling corrections. Methodologies have been developed to achieve effective levelling under these circumstances, although the final result varies depending on the methodology used. Data acquired on earlier surveys with control lines are being used to compare and contrast to data acquired without them. Ongoing power spectrum analysis suggests a way in which the different methods may be judged objectively. Horizontal components of gravity are also acquired by AIRGrav. Levelling these components is a challenge under all circumstances. The relationships between the components expressed in potential field theory allow the different components data to be compared and checked for consistency. Digital elevation model (DEM) data acquired during the surveys provide a means for checking other sources of DEM typically employed for applying terrain corrections. The impact of inaccurate DEM data on the corrected gravity data overall is small but can be locally significant. Data quality of the regional surveys is high, but the end user should be aware of the limitations posed by the choices made in data acquisition and processing.